Topical oxygen therapy as a novel strategy to promote wound healing and control the bacteria in implantology, oral surgery and periodontology: A review - Minas Leventis; Tatiana Deliberador; Fahad Alshehri; Hamdan Alghamdi (Saudi Dental Journal)
Globally, oral infections and inflammatory lesions persist as substantial public health concerns, necessitating the introduction of novel oral treatment protocols. Oral diseases are linked to various causative factors, with dental plaque/biofilm resulting from inadequate hygiene practices playing a predominant role. The strategic implementation of novel topical therapies holds promise for effectively controlling the biofilms, addressing oral infections and promoting enhanced oral wound healing. This review aims to providing a comprehensive overview of the available evidence pertaining to the potential efficacy of topical oxygen and lactoferrin-releasing biomaterials, exemplified by the blue®m formula, as novel oral care interventions within the scope of contemporary implantology, oral surgery and periodontology.